Impact of Covid‐19 pandemic on lifestyle in a middle‐aged and elderly population. (31st December 2021) - Wong, Zi Xuen; Phua, April; Chew, Kimberly Ann; Mohamed, Jameelah Sheik; Pérez, Kristal Morales; Mangialasche, Francesca; Kivipelto, Miia; Chen, Christopher
Abstract: Background: Mandated lockdowns and restricted activity in response to the COVID‐19 pandemic has affected our everyday life 1 . Seniors, in particular, have been affected due to higher morbidity and mortality 2 . The World‐Wide‐FINGERS‐SARS‐CoV‐2 survey is part of an international project, consisting of members of the World‐Wide FINGERS (WW‐FINGERS) Network for dementia risk reduction and prevention 3 . The study aims to measure the direct and indirect effects of the outbreak in midlife and older age. Preliminary results of this ongoing study is focused on lifestyle changes. Method: The survey commenced in September 2020.Participants aged 45 and above were recruited from existing research cohorts, memory clinic patients and community subjects. Sociodemographic factors, health related information, impact on lifestyle and behavior as well as personality factors were collected through three modalities: self‐administered online survey, telephone survey and in person with research staff. Result: At present, 167 non‐demented participants were included in the current preliminary analysis. Majority of the participants were Chinese (83.2%), aged 65 and above (59.3%), male (58.1%), with at least secondary education (80.8%). The survey found that 61.6% of the participants reported decreased contact with friends and relatives, with 22.2% reporting an increase in loneliness. Approximately one‐third of the participants reported a decrease in physical activity (35.9%) and an increase in food intake (30.5% in snacking habits; 25.1% in fruits consumption). Approximately half of the participants reported increase in usage of internet and digital services to keep in contact with family and friends. Conclusion: The COVID‐19 pandemic has produced measurable impacts on lifestyle‐related behavior of individuals. The decrease in social interaction and increase in loneliness during the pandemic due to government directive, along with concerns of contracting the virus highlight the importance of digital services for and digital literacy in older adults to keep them connected and supported remotely.